The Effectiveness of Sexual Transmitted Disease Education among Healthcare Workers and Non-Healthcare Workers - Prakoeswa, Flora Ramona Sigit; Dzikri, Dykall Naf'an; Wahidah, Wahidah (Faculty of Medicine, Universitas Airlangga, 2025)
Background: Sexually transmitted diseases (STDs) remain a significant global health concern. Education plays a crucial role in prevention, but its effectiveness may vary among different groups. Purpose: The purpose of this research was to determine how well both medical and non-medical staff at Dharma Wanita Orthopaedic Hospital Soeharso Surakarta understood sexually transmitted diseases, as measured by the STD-KQ questionnaire. Methods: This research employed a cross-sectional analytic observational design, involving 46 participants. Data were gathered through a sequence of pre-intervention assessment, educational program, and post-intervention evaluation. Statistical analysis was performed using paired t-tests and independent t-tests. Results: Prior to the intervention, healthcare workers possessed a significantly greater understanding of the subject matter (p=0.022). Both groups exhibited substantial improvements in their knowledge after participating in the educational program (p<0.05). The average scores for healthcare workers improved from 8.19 (± 4.80) to 16.15 (± 4.70), a statistically significant increase (p=0.001). Similarly, non-healthcare workers' scores rose from 13.40 (± 5.92) to 18.10 (± 4.24) (p=0.013). After the intervention, the initial difference in knowledge between the two groups was no longer statistically significant (p=0.154), indicating a closing of the knowledge gap. Conclusion: The educational intervention effectively improved STD knowledge in both groups and reduced the knowledge disparity between HCWs and NHCWs. The research points out the need for thorough and accessible sexual health instruction to improve STD understanding within diverse populations.